204k views
5 votes
Expand the binomial

(x-(4)/(5))^(2)

1 Answer

0 votes

Answer:


(x- (4)/(5))^(2) = x^2 -(8)/(5)x + (16)/(25)

Explanation:

You have two methods to expand this binomial.

Method 1

If you have the expression:


(x- (4)/(5))^(2)

You can write the expression it in the following way:


(x-(4)/(5))^(2)=(x-(4)/(5))(x-(4)/(5))

Then, apply the distributive property:


(x-(4)/(5))(x-(4)/(5)) = x^2 -(4)/(5)x -(4)/(5)x+ ((4)/(5))(4)/(5)

Simplify the expression:


(x-(4)/(5))^2= x^2 -(8)/(5)x+ ((16)/(25))

...........................................................................................................................................

Method 2

For any expression of the form:


(a-b)^2

Its expanded form will be:


(a-b)^2= a^2 -2ab + b^2

If


a = x


b =(4)/(5)


(x- (4)/(5))^(2) = x^2 - 2x(4)/(5) + ((4)/(5))^2


(x- (4)/(5))^(2) = x^2 -(8)/(5)x + (16)/(25)

User Njorden
by
5.6k points